Efektivitas Penganggaran Berbasis Kinerja Studi Kasus pada Satuan Kerja X OJK - Permata, Adinda Tisalita; Sinta, Sinta; Rossieta, Hilda (E-Jurnal Akuntansi, 2024)
This research aims to evaluate the implementation of performance-based budgeting in the Financial Services Authority (OJK) work unit, based on best practices in OECD countries that have implemented Performance-Based Budgeting (PBK) for decades. Evaluation of the implementation of PBK in work unit X OJK focuses on Goal Orientation, Human Resources and Information Technology factors. This research was carried out by analyzing regulatory documents and then confirmed with the real conditions of PBK at OJK through interviews with officials and staff who are authorized and competent in implementing budgeting at OJK. Interviews were conducted in October and November 2023. The research results show that OJK is at level 2 of the PBK classification for OECD countries,namely Performance-Informed Budgeting. At the Performance-Informed Budgeting level, where most OECD countries are located, budget implementation has been linked to performance information. Although goal orientation and human resources are considered effective, the level of effectiveness of Information Technology is relatively low. Keywords: Performance Based Budgeting;Public SectorAccounting.